Computer control : task synchronisation in dynamic priority scheduling - Lopes, Sérgio F. (1997)
Due to common resource protection, most real-time tasks have non-preemptive sections. Such sections, called critical sections, rise several problems to real-time scheduling theory. Namely, deadlock avoidance and bounded blocking time. Different and widely mentioned solutions exist for this problem in the context of fixed priority scheduling. However, solutions for the same problem but in the context of totally dynamic scheduling, although much more interesting, are seldom referred in the current literature. This paper surveys those solutions and illustrates their philosophies, providing thus a considerable help for real-time systems designers who develop or intent to develop their applications upon EDF or other totally dynamic scheduling algorithm.